(untitled) (Acta Polytechnica CTU Proceedings, 2020)
The investigations in this paper deal with the Cr-Ni alloy. The material has been recently proposed as a potential ATF concept, primarily due to its behaviour under high-temperature oxidation. A set of experiments to determine the melting point and describe the oxidation kinetics of the Cr-Ni alloy were performed in Karlsruhe Institute of Technology. Presented results reveal its superb oxidation resistance comparing to zirconium alloys. Therefore, the alloy has a great potential for nuclear applications.